The Relationship between social adjustment and scholastic achievement (A field study of a sample of children in the child-friendly space In Jermana) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The current research aims to identify the relationship between social adjustment of children and their degree of achievement. The impact of the sex variable is known in a segment of children whose families were displaced during the period of the Syrian crisis from the Damascus countryside to the city of Jaramana.The descriptive analytical approach was used in the field study and sample survey, which consisted of 100 child-friendly children and children in the city of Jaramana. The research tool consisted of a questionnaire to measure the social compatibility and educational achievement of children.,The research has reached a number of results, the most important of which are:-There is no significant correlation between the social adjustment of the sample and the academic achievement.-There was a statistically significant correlation between the social adjustment of female sample members and the academic achievement.-There was no statistically significant correlation between social adjustment of male sample members and academic achievement.[1] المساحة الصديقة للطفل بمدينة جرمانا: أحد مشاريع هيئة مار افرام السرياني البطريريكي للتنمية بدمشق